(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Abstract: The article explores the interplay between language and identity among Indigenous peoples, focusing on a study involving pre-service teachers learning Inuktitut. It highlights how language learning fosters cultural identity and enhances well-being, emphasizing that language encapsulates collective knowledge and strengthens connections to heritage. The research indicates that proficiency in Indigenous languages is crucial for maintaining cultural continuity and improving self-identity, particularly among youth. Additionally, it underscores the role of language in reinforcing community ties and belonging, which are vital for the overall health of Indigenous communities.